Determination the role of risk factor in neonatal jaundice disease at AL- Nasiriya city - ojs_admin (University of Thi-Qar Journal of Science, 2019)
Descriptive study was carried out to assess of neonatal jaundice in the sample consist of 150 patients selected fromBent – AL Huda hospital during ( 1- 10 -201 2 ) to ( 1- 10 -2013 ). Neonatal jaundice measured by application ofquestioners that designed by researchers themselves collected through personal interview of patients family as mean ofdata collection through use statistically tool( frequent, percentage , X2 ) and through use in program SPSS- V15 toanalysis data . The aim from the study is to determine risk factor of neonatal jaundice. The result revealed the incidenceof neonatal jaundice more in the male , low birth weight , NVD, breast feed , mother did not receive Anti – D finally themain recommendation should be monitor after birth the neonate have risk factor of jaundice .